2005
DOI: 10.1177/0733464804271455
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Care Initiatives for the Elderly: Can They Bridge the Gerontology-Medicine Gap?

Abstract: The authors describe initiatives designed to meet the chronic health needs of the elderly. These programs include demonstration programs such as Program of All-Inclusive Care for Elderly, Social Health Maintenance Organization, and state programs for Medicare-Medicaid-eligible elders that focus on integrating medical care with home and community-based services, diseaseor disability-focused care management/coordination initiatives, and recent population-based disease management programs focused on improving adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…2003, van Raak et al . 2003, Leichsenring & Alaszewski 2004, Lynch et al . 2005), and some key issues emerge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2003, van Raak et al . 2003, Leichsenring & Alaszewski 2004, Lynch et al . 2005), and some key issues emerge.…”
Section: Methodsmentioning
confidence: 99%
“…2004, Leichsenring 2004a, Nies 2005). Thus, traditional disease‐specific approaches may not be appropriate for older people with multiple symptoms (Lynch et al . 2005).…”
Section: Introductionmentioning
confidence: 99%
“… 2 However, an increasing proportion of the population has complex needs. This includes the older population with chronic diseases and multiple morbidities, 3 , 4 children born with complex conditions who are now living to adulthood, and people with learning disabilities who may need continuous care. 5 For these people, care delivery systems that are predominantly designed for acute illness may be both inappropriate and inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Canada, Beland et al's (2006a, 2006b RCT found that clients receiving an integrated, multidisciplinary service were less likely to be admitted to acute hospitals and once there, less likely to become 'bed blockers', that is, to be trapped in acute hospitals waiting for places in nursing home care. In the USA, Lynch et al (2005) discuss case studies of several innovations in addressing chronic health conditions that have the apparent potential to reduce costs, as well as providing better care for older people. They identify a tension between medical approaches, which they characterise as 'disease management', and services provided at home which tend to focus on function, or on supporting ability, and suggest that incentives are needed to promote service integration for such innovations to be successful.…”
Section: Models Of Carementioning
confidence: 99%